2016
DOI: 10.1111/vec.12449
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal dysmotility disorders in critically ill dogs and cats

Abstract: Objective -To review the human and veterinary literature regarding gastrointestinal (GI) dysmotility disorders in respect to pathogenesis, patient risk factors, and treatment options in critically ill dogs and cats. Etiology -GI dysmotility is a common sequela of critical illness in people and small animals. The most common GI motility disorders in critically ill people and small animals include esophageal dysmotility, delayed gastric emptying, functional intestinal obstruction (ie, ileus), and colonic motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 255 publications
(303 reference statements)
0
48
0
Order By: Relevance
“…One hundred percent RER is typically the maximum caloric target fed, as it has been shown that postoperative patients and critically ill patients do not have needs in excess of RER . In addition, gastrointestinal dysmotility is common in this patient population and is most often manifested as delayed gastric emptying and ileus . Delayed gastric emptying and ileus may predispose a patient to intolerance of tube feedings due to excessive gastric residual volume, vomiting, or regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred percent RER is typically the maximum caloric target fed, as it has been shown that postoperative patients and critically ill patients do not have needs in excess of RER . In addition, gastrointestinal dysmotility is common in this patient population and is most often manifested as delayed gastric emptying and ileus . Delayed gastric emptying and ileus may predispose a patient to intolerance of tube feedings due to excessive gastric residual volume, vomiting, or regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a dog with cricopharyngeal achalasia would require myectomy of the cricopharyngeous muscle while a dog with a hiatal hernia with consequent gastroesophageal reflux could be managed medically with prokinetic and acid suppressant therapy or via surgical reduction of the hiatus or both. Thus, a thorough understanding of the underlying cause(s) for dysphagia is imperative for formulating an appropriate therapeutic plan and prognosis …”
Section: Introductionmentioning
confidence: 99%
“…For a full review of these anti‐emetics, the reader is directed elsewhere (Vail ; Whitehead et al . ).…”
Section: Gastrointestinal Toxicitymentioning
confidence: 97%